Model Integratif-Kritis Pembentukan Hukum Kewarisan Islam di Indonesia: Analisis Sosio-Antropologis atas Dialektika Norma, Adat, dan Perubahan Sosial - Muhibbussabry; Dhiauddin Tanjung; Nispul Khoir; Imam Yazid (CV Global Research Publication, 2026)
Islamic inheritance law in Indonesia is shaped not only by faraidh norms, but also by state codification, customary practices, family legal culture, and social change. This article aims to analyze the formation of Islamic inheritance law in Indonesia through a socio-anthropological approach to the dialectic between norms, custom, and social transformation. This study employs qualitative library research with normative, statutory, sociology of law, legal anthropology, legal pluralism, and maqāṣid al-sharī‘ah approaches. The findings show that Islamic inheritance law in Indonesia is formed through layered negotiations among the certainty of faraidh, the reformative provisions of the Compilation of Islamic Law, family deliberation, kinship systems, local authority, and socio-economic needs. Custom may function as a mechanism of harmony, but it may also eliminate heirs’ rights when not accompanied by legal awareness, voluntary consent, and protection of vulnerable parties. This article proposes an integrative-critical model that positions faraidh as a normative anchor, while local practices may be accommodated insofar as they fulfill transparency of rights, clarity of property status, voluntary agreement, protection of vulnerable heirs, and maqāṣid-oriented benefit. This model affirms inheritance as both a legal norm and a dynamic, contextual social practice.